2017
DOI: 10.19105/ojbs.v11i2.1494
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Values of Liberal Feminism in Hillary Clinton’s Speech at the Democratic National Convention 2016

Abstract: In history, Hillary Clinton is the only female candidate as the president of the United State, and she got the name in politic, and having significant roles as a politician in America. Hillary performs a strong leadership and how the picture of women in the modern era. Thus, this study examines the representative women in the lens of Hillary Clinton. It is also under descriptively qualitative research supported by primary data from the script of Hillary Clinton's speech at the democratic national convention 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…He had the strength to face the challenging world. It is in line with (Fakhrian & Islamiyati, 2017) who found that a strong woman had been through challenges in her past life.…”
Section: Finding and Discussionsupporting
confidence: 83%
“…He had the strength to face the challenging world. It is in line with (Fakhrian & Islamiyati, 2017) who found that a strong woman had been through challenges in her past life.…”
Section: Finding and Discussionsupporting
confidence: 83%
“…From a liberal feminism perspective, every human being created in an equal position, harmonious, and having the same potency and rationality. Women need to be independent in every aspect to be equal to men (Fakhrian & Islamiyati, 2017). This point rejected the stereotyping of women as the other gender after men.…”
Section: Introductionmentioning
confidence: 99%
“…This point rejected the stereotyping of women as the other gender after men. According to a study conducted by Fakhrian and Islamiyati (2017), liberal feminism supports women assertive. It is in line with Tong's opinion that women should be able to break the stereotype that women should be submissive, thus to be emancipated, women should be forward and assertive in their life choices (Tong, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This type of research relies on the collection of qualitative data. It is explained that the characteristics of qualitative research are: data collected expressed in form of relative value and in general, the research done on social; allowing the author has an interpretation (Fakhrian, 2017).…”
Section: Methodsmentioning
confidence: 99%